2019
DOI: 10.1103/physrevd.99.063006
|View full text |Cite
|
Sign up to set email alerts
|

How post-Newtonian dynamics shape the distribution of stationary binary black hole LISA sources in nearby globular clusters

Abstract: We derive the observable gravitational wave (GW) peak frequency (f ) distribution of binary black holes (BBHs) that currently reside inside their globular clusters (GCs), with and without 2.5 Post-Newtonian (2.5PN) effects included in the dynamical evolution of the BBHs. Recent Newtonian studies have reported that a notable number of nearby non-merging BBHs, i.e. those BBHs that are expected to undergo further dynamical interactions before merger, in GCs are likely to be observable by LISA. However, our 2.5PN … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 98 publications
2
37
1
Order By: Relevance
“…Dynamically formed binaries are expected to feature several distinct sub-classes of formation channels that may also be distinguished by their eccentricities. In order of increasing characteristic formation frequency, these dynamical sub channels include: binaries dynamically ejected from their host cluster that merge as isolated binaries (f GW ≈ 10 −5 Hz), binaries that merge in cluster between strong dynamical encounters (f GW ≈ 10 −3 Hz), and finally binaries that merge in cluster through GW capture during single-single (f GW ≈ 10 −1 Hz) or few-body dynamical encounters encounters (f GW ≈ 1 Hz) (Breivik et al, 2016;Banerjee, 2018;Kremer et al, 2018a;Samsing and D'Orazio, 2018;D'Orazio and Samsing, 2018;Arca Sedda et al, 2021b;Samsing and D'Orazio, 2019;Kremer et al, 2019b;Zevin et al, 2019b;Banerjee, 2020;. Post-LISA-launch objective: Binaries formed through the ejected and in-cluster merger channels are expected to have eccentricities at GW frequencies of 10 −2 Hz of roughly 10 −3 and 10 −2 , respectively, which are expected to be measurable by LISA (Nishizawa et al, 2016).…”
Section: Neutron Star Equation Of Statementioning
confidence: 99%
“…Dynamically formed binaries are expected to feature several distinct sub-classes of formation channels that may also be distinguished by their eccentricities. In order of increasing characteristic formation frequency, these dynamical sub channels include: binaries dynamically ejected from their host cluster that merge as isolated binaries (f GW ≈ 10 −5 Hz), binaries that merge in cluster between strong dynamical encounters (f GW ≈ 10 −3 Hz), and finally binaries that merge in cluster through GW capture during single-single (f GW ≈ 10 −1 Hz) or few-body dynamical encounters encounters (f GW ≈ 1 Hz) (Breivik et al, 2016;Banerjee, 2018;Kremer et al, 2018a;Samsing and D'Orazio, 2018;D'Orazio and Samsing, 2018;Arca Sedda et al, 2021b;Samsing and D'Orazio, 2019;Kremer et al, 2019b;Zevin et al, 2019b;Banerjee, 2020;. Post-LISA-launch objective: Binaries formed through the ejected and in-cluster merger channels are expected to have eccentricities at GW frequencies of 10 −2 Hz of roughly 10 −3 and 10 −2 , respectively, which are expected to be measurable by LISA (Nishizawa et al, 2016).…”
Section: Neutron Star Equation Of Statementioning
confidence: 99%
“…The first 2 populations make up the broad peak at lower eccentricity, and the third results in the distribution at e 10 −2 seen for the gravitational-wave frequencies of f ref = 10.0 Hz and f ref = 1.0 Hz. At lower frequencies it is easier to distinguish between the ejected and in-cluster merger populations [133,326]; the dashed and dotted green lines differentiate the ejected and in-cluster populations, respectively, at f ref = 0.1 Hz. The peak near e ∼ 1 in the f ref = 10.0 Hz histogram is populated by systems that form in-band and merge on the timescale of days-years.…”
Section: Localizing Binaries and Identifying Their Host Environmentsmentioning
confidence: 99%
“…We expect that 3 rd generation detectors (Einstein Telescope [52][53][54], Cosmic Explorer [55]) will be operational in parallel with LISA, with SNR figures reaching hundreds or thousands, thus significantly improving the PE over current observations. Given the current uncertainty in the population of SBHBs, we cannot reliably specify the properties of most detectable sources [19,39,45,[56][57][58][59]. In our study we focus on a fiducial system consistent with the population of currently observed SBHBs instead of working with a randomized catalog of sources.…”
Section: Introductionmentioning
confidence: 99%